1998
DOI: 10.1086/305727
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of Ultracompact HiiRegions

Abstract: We present intermediate-resolution (j/*j B 60) spectra of 21 ultracompact H II regions in the spectral range from 3 to 13 km. The 9.7 km silicate feature is seen in absorption, and the 12.8 km [Ne II] Ðne structure line is seen in emission toward most of the observed nebulae. The strengths of both features vary enormously from nebula to nebula, suggesting large variations in the column densities of both Ne II and silicates toward these objects. Near-IR features attributed to polycyclic aromatic hydrocarbons (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
70
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 17 publications
14
70
1
Order By: Relevance
“…Campbell et al (2000) made radiative transfer models of the emission due to C and A in which a small amount of dust is located in or just outside the UC H ii regions. Very deep silicate absorption is present at these sources, as had also been observed by Faison et al (1998). This feature could not be due to self-absorption in the models of Campbell et al (2000), and they attributed it to an external absorbing cloud with a ' 3:5 at 20.6 m. Hatchell et al (2001) have recently concluded that the lack of MIR emission at the UC H ii component B is due to extremely strong extinction of the source.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Campbell et al (2000) made radiative transfer models of the emission due to C and A in which a small amount of dust is located in or just outside the UC H ii regions. Very deep silicate absorption is present at these sources, as had also been observed by Faison et al (1998). This feature could not be due to self-absorption in the models of Campbell et al (2000), and they attributed it to an external absorbing cloud with a ' 3:5 at 20.6 m. Hatchell et al (2001) have recently concluded that the lack of MIR emission at the UC H ii component B is due to extremely strong extinction of the source.…”
Section: Introductionsupporting
confidence: 52%
“…Models that are based on IRAS data but are not constrained by data on the source sizes typically have large central cavities with no dust, surrounded by one or more shells of uniform dust density, ¼ 0 (Chini, Krügel, & Kreysa 1986;Churchwell, Wolfire, & Wood 1990;Faison et al 1998). Models of high-and intermediate-mass deeply embedded young stellar objects that are based on SEDs covering MIR to millimeter wavelengths and are also constrained by KAO high-resolution scans in the FIR have a range in from 0 to 3, (Campbell et at.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the flux densities of Faison et al (1998) are lower than those of IRAS LRS as well as from ISO observations. This is because of the small aperture (9 ) of Faison et al (1998). The SED from the best fit radiation transfer model is shown in Fig.…”
Section: Radiation Transfer Calculationsmentioning
confidence: 74%
“…An attempt was made to fit the SED as well as the radial profile of the intensities. of IRAS 20178+4046 using the flux densities from balloonborne, IRAS and ISO observations, given in Tables 2 and 3, IRAS LRS data from Volks & Cohen (1989) and ground based observations of Faison et al (1998). This SED is shown in Fig.…”
Section: Radiation Transfer Calculationsmentioning
confidence: 99%
See 1 more Smart Citation